Strategi Penulisan Berita Guna Meningkatkan Mutu Pelayanan Informasi Bagi Publik - Erwan Efendi; Irfan Diki Wahyudi; Mairissa Zahra; Heri Hernanda Pandiangan; Aldi Ramdhani Gulo (Jurnal Pendidikan dan Konseling (JPDK), 2023)
News writing is a form of providing important information to the public. News delivered through mass media such as newspapers, television and the internet plays an important role in providing accurate, objective and useful information for the community. The quality of information services provided by the mass media is very important. Appropriate and accurate information will help people to make wise decisions, reduce uncertainty, and help overcome social and economic problems. Conversely, incorrect and inaccurate information can cause confusion, panic, and can even endanger public health and safety. Writing good and correct news is very important to improve the quality of information services for the public. Good news must meet criteria such as accurate facts, objective and unbiased delivery, and presented in clear and easily understood language by the public. In this era of digitalization, social media also plays an important role in providing information. Therefore, good news writing must also consider the influence of social media and how the information conveyed can impact society. Thus, good and correct news writing can improve the quality of information services for the public and help the public to make better and wiser decisions.